PENGARUH VARIASI LAMA WAKTU KONTAK DAN JUMLAH TANAMAN KAYU APU (Pistia stratiotes) TERHADAP PENURUNAN KADAR CADMIUM (Cd) LIMBAH CAIR BATIK HOME INDUSTRY “X” DI MAGELANG - Amalia Jamil; Yusniar Hanani Darundiati; Niki Astorina Yunita Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Home Industry Batik “X” in Magelang dispose of batik wastewater directly without wastewater treatment to the environmental. The batik wastewater containing heavy metals Cadmium (Cd), which can have a negative impact, both for environmental and health. The checking result of Cadmium (Cd) of batik wastewater is 1,317 mg/l this number is exceed the standart of Perda Jateng Number 5 2012 th. The purpose of this research to determine the effect of the contact time variations (6 day, 7 day and 8 day) and the number of water lettuce (6 clump and 8 clump) to reduced of  cadmium level  in wastewater of batik home industry "X". This type of research was the design of experimental pretest-posttest control group design with 3 treatment and 4 replications. The treatment used a batch system. Samples of wastewater used is partly wastewater staining batik home industry "X". Method of inspection Cd use Specthrofotometer Atomic Absorption (ASS). Decreased levels of Cd was highest in 8 day with 8 clump water lettuce, namely from 0,840 mg/l to 0,168 mg/l. This value is not below the quality standart that has been set in the amount of 0,1 mg/l. Friedman test results obtained significance value (p-value) = 0.001 (p <0.05), which showed a significant interaction effect between the contact time and the number of water lettuce to decrease  the levels of Cd in the waterwaste of batik. Efficiency of the highest decline in Cadmium reached 64,09% occured in treatment contact time of 8 day with 8 clump water lettuce.